Could Sex/Gender Differences in ACE2 Expression in the Lungs Contribute to the Large Gender Disparity in the Morbidity and Mortality of Patients Infected With the SARS-CoV-2 Virus? - Majdic, Gregor (Frontiers in Cellular and Infection Microbiology, 2020)
Covid-19 morbidity and mortality have significant gender disparity with higher prevalence and mortality in men. Sars-CoV-2 enters the lungs through the ACE2 enzyme, a member of the renin-angiotensin system (RAS). Although there is no data for lungs, expression of RAS components in other tissues are modulated by sex hormones, androgens and estrogens, but there is no data for sex-specific differences in ACE2 expression. If there is a sex difference in the expression of ACE2 in the lungs, this could theoretically explain the gender disparity in Covid-19 disease. More importantly, although modulation of ACE2 could certainly not provide the cure for the COVID-19 disease, modulation of ACE2 by sex hormone modulators, if they affect the expression of ACE2, could potentially be developed into the supportive therapy for Covid-19 patients.